Tastes, Preferences, Consumption and Purchasing Habits of Bread in The Bragança Region, Portugal - Letícia Cabrera Parra BORTOLUZZI; Maria Isabel Barreiro RIBEIRO; Adriana Aparecida DROVAL; António José Gonçalves FERNANDES (Communications of International Proceedings, 2020)
This study aimed to know the tastes, preferences and consumption and buying habits of bread in the Bragança region. A quantitative and cross-sectional study was developed based on a questionnaire applied online to 215 consumers who buy food products in the Municipality of Bragança. Most consumers were Portuguese (67%), female (61.9%), lived in urban areas (85.6%) and like bread (99.1%). Wheat bread (72.1%) and whole grain bread (64.7%) are the most consumed, despite not being bread from the Bragança region (47.9%). The three types of bread in the Bragança region that are best known and also the most consumed were Nogueira, Rebordainhos and Argozelo bread. Most consumers eat bread at least once a day (62.3%), 1 to 2 slices/small breads a day (76.7%), usually at breakfast (67.9%). The preferred type of accompaniment are vegetable fats (66.5%) and dairy (65.6%). The most valued attributes were the freshness (92.2%), the fresh bread smell (87.6%), the fluffy texture (80.8%), the crispy crust (76.1%), the price (56.2%) and the long lasting (55.2%). Most consumers buy bread at the supermarket (55.2%). The quality of the bread (96.9%) and the hygiene and cleaning of the space (93.7%) are the factors most valued by the consumers at the time of the purchase. Taking into account the nationality, differences were identified in the type of bread consumed, the time of consumption and the chosen accompaniment. In fact, foreigners prefer to consume whole grain bread and special bread with cheese or cottage cheese at any time of the day. Portuguese consumers prefer rye or brown bread with jam or honey.
Keywords: Bread; Consumption habits; Consumer; Market research.